Efficacy of Plant- Powders Against Rice Weevil, Sitophilus oryzae (Linnaeus) (Curculionidae: Coleoptera) at Laboratory Condition (SAARC Journal of Agriculture, 2022)
An experiment was conducted to evaluate the efficacy of plant-based repellent powders for S. oryzae at the National Rice Research Program, Hardinath, Dhanusha, Nepal in 2020 at laboratory condition. Two hundred gram of paddy grains of cv. Sambha Mansuli Sub-1 was kept in each plastic jar in the experiment. Ten pairs of newly emerged adult rice weevil, S. oryzae of uniform age obtained from stock culture were released in each plastic jar. Laboratory bioassay contained Acorus calamus (rhizome powder) @10 gm/kg, Piper nigrum (seed powder) @10 gm/kg, Curcuma longa (rhizome powder) @10 gm/kg, Azadirachta indica (kernel powder) @ 10gm/kg, Zingiber officinale (rhizome powder) @10 gm/kg, and Malathion powder 5% dust @2 gm/kg were used for the rice weevil. Acorus calamus was the most effective botanical powder followed by P. nigrum to reduce grain damage percent on number basis (1.15%) and on weight basis (1.22%), weight loss percent (0.84%) & weevil population count (1.54). The efficacy ranks of the botanicals were: A. calamus>P. nigrum>A. indica>Z. officinale>C. longa. Thus, use of A. calamus powder is recommended to manage rice weevil in the storehouse condition.SAARC J. Agric., 19(2): 331-338 (2021)